A socialização escolar na concepção de professores da rede municipal de ensino de Goiânia-GO - MENDANHA, Sílvia do Socorro (2011)
The modern concept of childhood is simultaneously consolidated with the conformation of the bourgeois family and the organization of education at school, in capitalist society; in turn, this reorders the understanding and purpose of socialization processes. Inserted in that context, school is the privileged locus to promote the process of child`s socialization, which assumes a character of adaptation and integration, during the physical pass from childhood to adulthood. This perspective, becoming predominant at that time, enables the characterization and reorientation of both, either the bourgeois family or school; thereafter, school becomes the responsible instance for introducing the egress child, from family into social environment. Nevertheless, socialization process does not begin merely when child goes to school; during the process of growing, and later on, in adulthood, child participates of multiple socialization instances, as religion, political parties, technologies, groups of friends, among others. In spite of those, the instance of socialization at school is herein privileged, as it constitutes itself as the object of this work study. School has been named as the main institution for the establishment of child`s socialization process. This research objectifies to discuss the socialization processes under above perspective, and their interface with education at school, rending problematic which is the socialization concept of Goiania Municipal teachers` network. To develop such a research, methodological resources were bibliographic research, as well as an empirical survey, held with the application of a questionnaire, to a group of sixteen teachers, at four schools. After the systematization and apprehension of the theoretical referential, the answers have been categorized and the analysis of empirical data has been conducted, based on theoretical reference, objectifying to capture the multiple dimensions of that reality, as well the most relevant and significant trends in what concerns teachers` conceptions of socialization processes at school. Conclusions point to the predominance of the conception of socialization as integration, according to teachers